A new species of Wongia (Papulosaceae, Sordariomycetes) from Taiwan - Kuo, Chang-Hsin; Hsieh, Sung-Yuan; Goh, Teik-Khiang (Phytotaxa, 2024)
Wongia miscanthi sp. nov. from decaying culms of Miscanthus floridulus submerged in freshwater streams at Wufeng District, Taiwan, is described and illustrated, based on two collections. This new species was identified based on morphological comparison and multi-locus phylogenetic analyses of combined ITS, LSU, SSU, rpb2, and tef1a sequence dataset. Intraspecific variability between the two collections is discussed. A synopsis of Wongia species is compiled for comparison and a taxonomic key to the species is provided as an aid to their identification.